Load balancing technique using semiconductor devices / Azmi Ismail - Ismail, Azmi (1992)
Load balancing system which employed diode rectifier and MOSFET inverter was presented and designed. The purpose of the this project is to shift the current from one load line to another load line of the three phase supply so that the supply would be balanced if viewed from the load side. The excess current being rectified and converted to AC using inverter with reference to the angle of the second line. Other areas of investigation observed were the characteristics of the supply voltage and also the load voltage, the selection of the components for the above project. Finally, predicted results were verified through the experiment.